The Meskwaki and anthropologists : Action Anthropology reconsidered - Daubenmier, Judith M. (Critical studies in the history of anthropology., 2008)
The Meskwaki and Anthropologists illuminates how the University of Chicago's innovative Action Anthropology program of ethnographic fieldwork affected the Meskwaki Indians of Iowa. From 1948 to 1958, the Meskwaki community near Tama, Iowa, became effectively a testing ground for a new method of practicing anthropology proposed by anthropologists and graduate students at the University of Chicago in response to pressure from the Meskwaki. Action Anthropology, as the program was called, attempted to more evenly distribute the benefits of anthropology by way of anthropologists helping the Native.